Attrition and weight loss outcomes for patients with complex obesity, anxiety and depression attending a weight management programme with targeted psychological treatment. Issue 2 (3rd February 2016) - McLean, R. C.; Morrison, D. S.; Shearer, R.; Boyle, S.; Logue, J.
Summary: The objective of the study is to investigate the effect of baseline anxiety and depression, using different definitions for caseness, on attrition and weight outcomes following a multidisciplinary weight management programme. The study design is a prospective observational study. The Hospital Anxiety and Depression Scale (HADS) was used to measure anxiety and depression with 'caseness' scoring ≥11 and severity ≥14. The participants were all patients who began a weight management programme between 1 October 2008 and 30 September 2009 ( n  = 1838). The setting was the Glasgow and Clyde Weight Management Service (GCWMS), a specialist multidisciplinary service, which aims to achieve a minimum of ≥5 kg weight loss. The results were as follows: patients with HADS score ≥14 were referred to the integrated psychology service for psychological assessment or intervention. Patients with caseness (HADS ≥11) for anxiety (33%) and depression (27%) were significantly younger, heavier, more socio‐economically deprived and a higher proportion was female. There was a significant positive correlation between HADS anxiety and depression scores and increasing body mass index (r 2  = 0.094, P  < 0.001 and r 2  = 0.175, P  < 0.001, respectively). Attendance and completion was lower throughout follow‐up amongst patients with anxiety or depression. More patients with HADS score ≥11 achieved ≥5 kg or ≥5% weight loss and by 12 months those with anxiety had a significantly higher mean weight loss ( P  = 0.032). Participants who scored for severe anxiety (HADS ≥14) achieved similar weight loss to those without, whilst participants who scored for severe depression achieved significantly greater weight loss than non‐cases at 3, 6 and 12 months of follow‐up ( P  < 0.01). Despite a less favourable case‐mix of risk‐factors for poor weight loss, patients who scored caseness for severe anxiety or depression and were offered additional psychological input achieved similar or better weight loss outcomes.